Reading LXXJudith 13:1–9 as performance - Allen, Nicholas P. L. (HTS teologiese studies, 2020)
The Septuagint Book of Judith and its derivatives have had an enormous influence on the history of Western Europe and the Christian church. Judith has been employed in various situations to incite violence against a perceived opposition. In this regard, this article focuses on the climax of this book (Jdt 13:1–9) as performance text. In this context, many of the insights proffered by Perry in his seminal work Insights from Performance Criticism (2016) have been expanded upon from the perspective of a Greek and/or Hellenistic environment.Contribution: The value of reading LXXJudith as performance is clearly demonstrated. The conclusion is reached that this pericope is indeed highly subversive. Suggestion is also made that, contrary to more conservative wisdom, with reference specifically to LXXJudith 13:1–9, the Judith fabula is not really reconciliatory in nature. Rather, it seems to provoke conflict between competing powers.